MANAGEMENT BY OBJECTIVES AND ITS ROLE IN THE PERFORMANCE OF EMPLOYEES IN SPORTS ACTIVITIES AT SELECTED IRAQI UNIVERSITIES (Proximus Journal of Sports Science and Physical Education, 2024)
This study aimed to assess the level of implementation of management by objectives (MBO) in university sports activities at selected Iraqi universities and to explore the role of using the MBO approach in the performance of employees engaged in sports activities in these institutions. The study sample consisted of 380 employees selected from the study population. A questionnaire was used as the primary tool for data collection, and several statistical analyses were employed, including arithmetic means and normality tests. The results indicated the following: 1. The level of implementation of MBO in university sports activities at selected Iraqi universities was moderate. This is attributed to the comprehensiveness of the MBO elements as a performance evaluation tool, its accuracy, and the clarity of its content. 2. Statistically significant differences were found regarding the use of the MBO approach in the performance of employees involved in university sports activities at selected Iraqi universities.